The Economic Effects of the Gold Discoveries Upon South Africa: 1886-1910 - Gilbert, Donald Wood (Quarterly Journal of Economics, 1933)
Introductory survey, 553.— Development of the gold industry, 557.— Capital imports and their timing, 560.— The expansion of purchasing power, 567.— Price movements: foods, 570; house rents, 572; imports, 574; exports, 574; complications, 576.— Money incomes, 578.— Immigration, 582.— The balance of payments, 583.— Trade statistics, 585.— Other items in the balance, 587.— The terms of trade, 588.— Comparative advantages and disadvantages: exports, 590; imports, 592; production, 593.— Conclusion, 596.